Short communication: Timber harvesting impacts small mammal foraging behavior and larval tick infestation - Stephanie N. Hurd; Allison M. Gardner (PLoS ONE, 2025)
Small mammals are important blood-meal hosts for the blacklegged tick, Ixodes scapularis, and reservoirs for the pathogens it transmits. Timber harvesting, a widespread forest management practice within I. scapularis’s endemic range, may impact tick densities and infection prevalence via effects on rodent communities. We compared rodent population size, activity patterns, tick burdens, and tick-borne pathogen infection rates in forests under different timber harvesting regimes. We found that harvest intensity correlates negatively with rodent foraging intensity and positively with tick burdens. Thus, host behavior may mechanistically link forest structure to tick densities in managed forests.